Feasible predictions of bone remodelling using modelling techniques - Klika, V; Maršík, František (Pohybové ústrojí. Pokroky ve výzkumu, diagnostice a terapii, 2011)
This manuscript gives an overview of our team effort to formulate a bone remodelling model that would comprise both crucial control mechanisms in this process: RANKLRANK- OPG pathway and (dynamic) loading. Main focus is aimed at how model of interdisciplinary problem can be tracked down and how its results and analysis may provide valuable information hopefully not only to mathematicians but to clinicians as well. Modelling is always a theoretical work that is always built upon some simplifications and assumptions which lead to intrinsic limitations of the model that need to be found. Here we provide feasible results that can be obtained through our approach and offer them to discussion.
Keywords: financování organizované; Statistics as Topic; teoretické modely; statistika jako téma; parathormon; kostní denzita; Bone Density; lidé; remodelace kosti; mechanické jevy; Financing, Organized; biomechanika; Parathyroid Hormone; Nitric Oxide; Thermodynamics; Bone Remodeling; Mechanical Phenomena; oxid dusnatý; Estradiol; RANK Ligand; termodynamika; Models, Theoretical; ligand RANK; Biomechanical Phenomena; estradiol; Humans